ҮСТИРТТЕН ТАБЫЛҒАН АЙҚАЛ ЕСТЕЛИГИНЕ БАЙЛАНЫСЛЫ БАЗЫБИР МАҒЛЫЎМАТЛАР - Қанаатов, Е.Е. (FAN va JAMIYAT, 2023)
This article is devoted to anthropomorphic stone statues found in the vastness of Ustyurt. Balbals, which has long been popular among the Turkic peoples, is also called aikal in the Karakalpak language. These stones were erected in honor of the deceased elders, heroes or other famous people. According to studies, the stone statues found in Ustyurt are older than the ancient balbal of the Turkic world and turned out to be a monument of the 5th-2nd centuries BC. Two of these ancient aikals found in Ustyurt were brought to Karakalpakstan, and one of them is kept in the archaeological museum of the Karakalpak branch of the Academy of Sciences of Uzbekistan. In scientific works, it is noted that these sculptures are associated with the traditions of the Sak-Massagets.